2020
DOI: 10.1186/s12909-020-02422-9
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ self-reported gender discrimination and sexual harassment over time

Abstract: Background Gender discrimination (GD) and sexual harassment (SH) occur at all academic institutions worldwide. Medical students report high prevalence of GD and SH, which may negatively affect their education and health. There are indications that policies and reforms on reducing GD/SH are insufficient. Swedish medical students’ experiences of GD/SH are monitored by course-evaluations and bi-annual student union evaluations; however, the response rate is usually low. The aim of this study was t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 32 publications
3
9
1
1
Order By: Relevance
“…These comments showed how schools had become a place for gender-based harassment and the concerned authorities were found ignoring their responsibilities to prevent such activities. This is similar to the findings Kisiel et al (2020) who compared that found that the ratio of gender discrimination and sexual harassment sharply increased for female compared to male students in Swedish schools. Similarly, due to regular gender-based harassment at schools, I found some girls increased their irregularity and decreased their learning achievement.…”
Section: Sexual Harassmentsupporting
confidence: 91%
“…These comments showed how schools had become a place for gender-based harassment and the concerned authorities were found ignoring their responsibilities to prevent such activities. This is similar to the findings Kisiel et al (2020) who compared that found that the ratio of gender discrimination and sexual harassment sharply increased for female compared to male students in Swedish schools. Similarly, due to regular gender-based harassment at schools, I found some girls increased their irregularity and decreased their learning achievement.…”
Section: Sexual Harassmentsupporting
confidence: 91%
“…These results match those reported by previous research, which alludes to the high rates of sexual harassment in medical students. It is considered that the dependence of medical students on their supervisors, particularly women medical students, is a risk factor for sexual harassment and gender discrimination, which promotes exposure to abuse during medical training [ 26 , 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Questions explored participants' familiarity with reporting systems, experience using reporting systems, barriers to utilizing reporting systems (both personally experienced and experienced by colleagues), perceptions of departmental support of reporting processes, and potential improvements to reporting systems. The interview guide was informed by the study team's experiences as women EM physicians (all study team members are women, representing women residents, junior faculty, and midcareer faculty) and incorporated existing evidence from literature related to the topic of gender and sexual harassment 1–6,8–11,14,15 . Prior to the study, the interview guide was piloted with EM residents and faculty, both men and women, and refined to verify that questions were appropriately understood by participants.…”
Section: Methodsmentioning
confidence: 99%
“…
Gender and sexual harassment in academic medicine is persistent and pervasive. [1][2][3] Six in 10 medical trainees reported sexual harassment or discrimination during their training; within emergency medicine (EM), over half (53%) of women faculty and one in four (26%) men faculty have experienced some form of gender or sexual harassment in their workplace. 4,5 Gender and sexual harassment in clinical settings has severe adverse consequences for both survivors and health systems.
…”
mentioning
confidence: 99%